In the quest for dominance in East Asia: Evolution of economic position of Japan and China - Pasierbiak, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The subject of this study is the economic changes in East Asia that took place after the Asian financial crisis (1997). The largest economies in the region, Japan and China, are competing for economic primacy which would allow them to better realize their own set of preferences. China has challenged the existing economic leader – Japan, quite successfully gaining preeminent positions in various areas of the region’s economy. This paper presents changes taking place in basic spheres of economic activities of countries, namely: production, foreign trade and FDI flows. The author, using the descriptive method and the method of analysis, interpretation and inference based on statistical data, positively validates the hypothesis of China’s increasingly prevalent economic role over Japan in East Asia after the Asian crisis. The analysis covers the timespan 1997–2015
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 49-60
Keywords: East Asia; China; Japan; economic dominance; Azja Wschodnia; Chiny; Japonia; dominacja gospodarcza